Total quality management and business process reengineering applications and foundation of a quality assurance system in service sector - Güler, Murat Gökhan (My University, 1997)
unknown
Keywords: DEĞİŞİM MÜHENDİSLİĞİ; TOPLAM KALİTE YÖNETİMİ